Prevalence and impact of concomitant malignancy on outcomes among ambulatory heart failure population. (29th August 2020) - Shuvy, Mony; Zwas, Donna R.; Keren, Andre; Gotsman, Israel
Abstract: Introduction: Heart failure (HF) and cancer are medical conditions with a rising prevalence resulting in increased co‐occurrence. We assessed the impact of cancer on clinical outcome in patients with HF and the prognostic impact of specific types of cancers on different HF subpopulations. Methods: All patients with HF were evaluated for the occurrence of malignant neoplasm at a health maintenance organization and were followed for cardiac‐related hospitalizations and death. Results: The study cohort included 7106 HF patients, 1564 of them (22%) had a diagnosis of malignant neoplasm. HF patients with concomitant cancer were older, had more comorbidities and were more likely to have NYHA class III/IV (42% vs. 37%, P  < .01), compared with patients with no malignancy. The overall 2‐year mortality rate of the entire HF cohort was 23.2%. Survival rate by Kaplan‐Meier analysis demonstrated that the presence of a malignancy was directly associated with reduced survival: 67.2 ± 1.2% vs 79.5 ± 0.5%, P  < .001. Malignancy was associated with an increase in mortality with a hazard ratio (HR) of 1.36, 95% confidence interval (CI) 1.21‐1.54, P  < .001. The strongest impact of malignancy on outcomes was related to age; among patients <70 years old, the increase in the risk of mortality was the highest with a HR of 2.07, 95% CI 1.54‐2.80, P  < .001. Conclusions: Malignancy is common among patients with HF. Patients with concomitant HF and malignancies have poor outcomes, and the impact of cancer on outcome is stronger among young patients.